COMMON CRITERIA AND METHODOLOGIES FOR SELECTING LANDFILL SITES - Musayeva Mehriniso Hamro qizi (Miasto Przyszłości, 2023)
This article explores the common criteria and methodologies used in the selection of waste landfill sites in the Surkhandarya region. Proper waste disposal is crucial for environmental protection and public health. The study reviews existing literature, presents a methodology for site selection, and discusses the results, emphasizing the importance of sustainable landfill site selection.